Strategic Plan 2018-21 (CCRIF SPC Grand CaymanKY, 2018)
The CCRIF Strategic Plan 2018-21 is based on CARICOM's bold ambition to make the Caribbean the first climate-resilient zone in the world. CCRIF has committed to helping the region realise this ambition.